Interpretasi terkini data arkeologi di kompleks percandian Pengkalan Bujang, Kedah - Ramli Zuliskandar, Nik Abdul Rahman Nik Hassan Shuhaimi, Jusoh Adnan, Razman Muhammad Rizal (N/A, 2014)
Interpretasi terkini data arkeologi di kompleks percandian Pengkalan Bujang, Kedah by Ramli Zuliskandar, Nik Abdul Rahman Nik Hassan Shuhaimi, Jusoh Adnan, Razman Muhammad Rizal,